Operación de motores trifásicos mediante la utilización de un controlador lógico programable. - Solano, Wittman Pablo. (2010)
In the development of this technical report, different methods and research techniques have been used, which have provided me with a better knowledge for the implementation of a didactic dashboard for automation through the use of a mini-PLC LOGO! 230 RC industrial. The dashboard is designed to carry out electric motor control practices, has two three-phase motors, run and stop buttons, protection elements and a mini-PLC LOGO! 230 RC. This work will serve as a guide for students to have more knowledge about the operation of three-phase motors and the use of the LOGO! 230 RC. Its use is mainly in those facilities where a process of maneuvering, control, signaling, etc. is required, therefore, its application ranges from industrial manufacturing processes of any type to industrial transformations, facility control, etc. Their reduced size, the extreme ease of assembly, the possibility of storing the programs for their later and rapid use, the modification or alteration of them, etc., makes their efficiency to be appreciated fundamentally in processes in which such necessities occur Such as: Reduced space, Periodically changing production processes, Sequential processes, Variable process machinery, Complex and wide process facilities, Centralized programming check of the parts of the process. The practices are designed, through a guide, so that the students do them in a simple and fast, which will have repercussion in a better appropriation of the knowledge. For the accomplishment of the present work I have raised the following objectives: Design a unit that operates two Asynchronous Three-phase Motors using a Programmable Logic Controller and learn some of the functions of the mini-PLC. Provide an automation equipment to the electrical workshop so that students can practice and increase their academic knowledge. Perform practices using the basic and special functions provided by the mini-PLC, thus demonstrating its quick and easy handling.